Omental metastases in patients with pseudomyxoma peritonei or colorectal peritoneal metastases – is routine omentectomy justified? - Malin Enblad; Helgi Birgisson; Lana Ghanipour; Peter Cashin; Wilhelm Graf (International Journal of Hyperthermia)
Background The greater omentum is routinely resected during cytoreductive surgery (CRS), but few studies have analyzed the rationale behind this. This study aimed to assess the prevalence of omental metastases (OM) and the correlation between macroscopically suspected and microscopically confirmed OM, in patients with pseudomyxoma peritonei (PMP) or colorectal peritoneal metastases (PM).Method All patients without previous omentectomy, treated with initial CRS and hyperthermic intraperitoneal chemotherapy for PMP or colorectal PM, at Uppsala University Hospital in 2013–2021, were included. Macroscopic OM in surgical reports was compared with histopathological analyses.Results In all, 276 patients were included. In those with PMP, 112 (98%) underwent omentectomy and 67 (59%) had macroscopic suspicion of OM. In 5 (4%) patients, the surgeon was uncertain. Histopathology confirmed OM in 81 (72%). In patients with macroscopic suspicion, 96% had confirmed OM (positive predictive value, PPV). In patients with no suspicion, 24% had occult OM (negative predictive value, NPV = 76%). In patients with colorectal PM, 156 (96%) underwent omentectomy and 97 (60%) had macroscopic suspicion. For 5 (3%) patients, the surgeon was uncertain. OM was microscopically confirmed in 90 (58%). PPV was 85% and NPV was 89%. The presence of OM was a univariate risk factor for death in PMP (HR 3.62, 95%CI 1.08–12.1) and colorectal PM (HR 1.67, 95%CI 1.07–2.60), but not in multivariate analyses.Conclusion OM was common and there was a high risk of missing occult OM in both PMP and colorectal PM. These results support the practice of routine omentectomy during CRS.